Modeling inequity aversion in a dictator game with production - Ismael Rodriguez-Lara; Luis Moreno-Garrido (Games, 2012)
We expand upon the previous models of inequity aversion of Fehr and Schmidt [1], and Frohlich et al. [2], which assume that dictators get disutility if the final allocation of surplus deviates from the equal split (egalitarian principle) or from the subjects' production (libertarian principle). In our model, dictators may also account for the way in which the surplus was generated. More precisely, our model incorporates the idea of liberal egalitarian ethics into the analysis, making it possible for dictators to divide the surplus according to the accountability principle, which states that subjects should only be rewarded for factors under their control. This fairness ideal does not hold subjects responsible for factors beyond their control in the production of the surplus, an idea that is absent in the models of inequity aversion cited above
Keywords: D3; D6; D63; 330; social preferences; inequity aversion; inequality aversion; egalitarian principle; libertarian principle; accountability